The Discourse of Spirituality Versus Religiosity in Islam - Idi Warsah; Imron Imron (Graduate Program of Pontianak Institute of Islamic Studies, 2019)
This article discusses spirituality and religiosity. Spirituality and religiosity are two of the most basic aspects of mentality and human belief, which according to most people are the goal of human existence in the world. These two terms are widely understood by people as something that has the same meaning and understanding. But actually has a different meaning. Spirituality is an experience or desire to know God that is done personally by seeing things deeper, substantially and seeking real understanding. Whereas religiosity is the appreciation and experience of individuals towards the teachings of religion or the beliefs they hold. Therefore, in essence, religiosity is a pattern of values, beliefs, symbols, behavior and experience that is institutionalized, which is directed at spirituality. In this case religiosity is actually a means of achieving spirituality.